2022
DOI: 10.1038/s41598-022-18304-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of 3D Darcy–Forchheimer fluid flow with the energy and mass transfer over an irregular permeable surface

Abstract: The Jeffrey fluid model is capable of accurately characterizing the stress relaxation behavior of non-Newtonian fluids, which a normal viscous fluid model is unable to perform. The primary objective of this paper is to provide a comprehensive investigation into the effects of MHD and thermal radiation on the 3D Jeffery fluid flow over a permeable irregular stretching surface. The consequences of the Darcy effect, variable thickness and chemical reaction are also considered. The phenomena have been modeled as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Ahmed et al [10] used the Adomian decomposition approach to observe the flow of Jeffery fluid through an extending or contracting sheet. Algehyne et al [11] used the numerical technique to elaborate the impact of nanoliquid flow across a porous extending substrate. It has been observed that the permeability factor, heat flux, and Newtonian heating increase the energy efficiency rating while the power indices and Deborah number have the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [10] used the Adomian decomposition approach to observe the flow of Jeffery fluid through an extending or contracting sheet. Algehyne et al [11] used the numerical technique to elaborate the impact of nanoliquid flow across a porous extending substrate. It has been observed that the permeability factor, heat flux, and Newtonian heating increase the energy efficiency rating while the power indices and Deborah number have the opposite effect.…”
Section: Introductionmentioning
confidence: 99%